Nowhere to be found - Suah, Bae 1965- (AmazonCrossing, 2015)
A nameless narrator passes through her life, searching for meaning and connection in experiences she barely feels. For her, time and identity blur, and all action is reaction. She can’t quite understand what motivates others to take life seriously enough to focus on anything—for her existence is a loosely woven tapestry of fleeting concepts. From losing her virginity to mindless jobs and a splintered, unsupportive family, the lessons learned have less to do with the reality we all share and more to do with the truth of the imagination, which is where the narrator focuses to discover herself.